2009
DOI: 10.1593/tlo.08187
|View full text |Cite
|
Sign up to set email alerts
|

α5β1 Integrin Ligand PHSRN Induces Invasion and α5 mRNA in Endothelial Cells to Stimulate Angiogenesis

Abstract: Angiogenesis requires endothelial cell invasion and is crucial for wound healing and for tumor growth and metastasis. Invasion of native collagen is mediated by the alpha(5)beta(1) integrin fibronectin receptor. Thus, alpha(5)beta(1) up-regulation on the surfaces of endothelial cells may induce endothelial cell invasion to stimulate angiogenesis. We report that the interaction of alpha(5)beta(1) with its PHSRN peptide ligand induces human microvascular endothelial cell invasion and that PHSRN-induced endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Numerous studies demonstrated that α5β1-integrin expression levels are altered in many types of cancer (Morozevich et al, 2009), there may be involved in modulating effect on several signalling pathways ,which are closely related to the regulation of cell survival, proliferation ,differentiation and apoptosis, and in stimulating tumor angiogenesis (Zeng et al, 2009) Although it has been shown that α5β1-integrin …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies demonstrated that α5β1-integrin expression levels are altered in many types of cancer (Morozevich et al, 2009), there may be involved in modulating effect on several signalling pathways ,which are closely related to the regulation of cell survival, proliferation ,differentiation and apoptosis, and in stimulating tumor angiogenesis (Zeng et al, 2009) Although it has been shown that α5β1-integrin …”
Section: Introductionmentioning
confidence: 99%
“…Although the death rate for cervical cancer has decreased dramatically since the introduction of cervical cytology as a widespread screening procedure, the survival rate at advanced stages of disease has not improved. Therefore, characterization of identifiable molecular markers may play an important role in understanding of molecular pathogenesis and in identifying latently prognostic biomarkers for cervical cancer.Numerous studies demonstrated that α5β1-integrin expression levels are altered in many types of cancer (Morozevich et al, 2009), there may be involved in modulating effect on several signalling pathways ,which are closely related to the regulation of cell survival, proliferation ,differentiation and apoptosis, and in stimulating tumor angiogenesis (Zeng et al, 2009) Although it has been shown that α5β1-integrin …”
mentioning
confidence: 99%
“…Despite demonstrating a strong correlation between α5β1-integrin expression and tumor occurrence, development and metastasis, the possible mechanism responsible for this association is that α5β1-integrin stimulate tumor angiogenesis [25].In addition to mediating cell adhesion, integrins make transmembrane connections to the cytoskeleton and activate many intracellular signaling pathways [26,27].The α5β1-integrin/fibronectin interactions may influence also cell survival by modulating apoptosis. In addition, α5β1-integrin signalling can promote also cell survival by up-regulation of anti-apoptotic proteins [28,29], or suppression of apoptotic mediators [30].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that integrin and MMPs had mutual effect .These findings suggested that α5β1-integrin plays a functional role in the invasion of studied cells, perhaps by triggering a signaling pathway controlling the activity of MMP-14 gene. Most importance was that α5β1-integrin and MMP-14 also have the common functions of activating MMP-2 [39][40][41][42] and stimulating tumor angiogenesis [25,43]. The α5β1-integrin and MMP-14 could promote each other in tumor with invasion and metastasis process and act synergistically.…”
Section: Discussionmentioning
confidence: 99%
“…The Arginine amino acid in the original sequence is replaced with cysteine residue. ATN-161 induces neovascularization in matrigel plug assays performed in nude mice and observed a dose dependent regulation of α 5 β 1 integrin in human microvascular endothelial cells [73]. These down regulation of α 5 β 1 integrin resulted in apoptosis through the suppression of the Akt activity [74].…”
Section: Integrin Antagonists In Tumor and Angiogenesis Inhibitionmentioning
confidence: 95%